Desert Editorial Revolution Hinders Revolutionary Organization and Natural Ocean Challengrs - hoggari, mohammed (The Algerian Historical Journal, 2026)
The content of the article attempts to answer many questions related to political and social causes and natural challenges that delayed and prevented the arrival of the 1954 national liberation revolution and its extension to the far south of Algeria. The article also clarifies and highlights the strategy adopted by the National Liberation Front (FNL) to establish the foundations and bases of revolutionary organization cells in the Sahara, beginning with the process of framing and mobilizing the population to engage in the armed struggle. and in order to challenge the difficulties of the geographical environment, defying all the schemes of the French colonial administration and its agents aimed at scuttling this noble national mission and addressing the mujahedeen who took it upon themselves to achieve and accomplish it.